Kidney Exchange Match Rates in a Large Multicenter Clearinghouse - Holscher, Courtenay M (Am J Transplant, 2018)
Kidney paired donation (KPD) can facilitate living donor transplantation for candidates with an incompatible donor, but requires waiting for a match while suffering the morbidity of dialysis. The balance between waiting for KPD versus desensitization or deceased donor transplantation relies on the ability to estimate KPD wait times. We studied donor/candidate pairs in the National Kidney Registry (NKR), a large multi-center KPD clearinghouse, between 10/2011-9/2015 using a competing risk framework. Among 1894 candidates, 52% were male, median age was 50 years, 66% were white, 59% had blood type O, 42% had PRA>80, and 50% obtained KPD through NKR. Median times to KPD ranged from 2 months for candidates with ABO-A and PRA 0, to over a year for candidates with ABO-O or PRA 98+. Candidates with PRA 80-97 and 98+ were 23% (95% CI: 6-37%) and 83% (78-87%) less likely to be matched than PRA 0 candidates. ABO-O candidates were 67% (61-73%) less likely to be matched than ABO-A candidates. Candidates with ABO-B or ABO-O donors were 31% (10-56%) and 118% (82-162%) more likely to match than those with ABO-A donors. Providers should counsel candidates about realistic, individualized expectations for KPD, especially in the context of their alternative treatment options.